2007
DOI: 10.2519/jospt.2007.2467
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Scapular Taping on the Surface Electromyographic Signal Amplitude of Shoulder Girdle Muscles During Upper Extremity Elevation in Individuals With Suspected Shoulder Impingement Syndrome

Abstract: Normal muscular control of the scapula is important for activities involving upper extremity (UE) elevation. The upper and lower trapezius and the serratus anterior muscles have important and specific roles in upward rotation of the scapula during UE elevation.2,3,18,28 Muscular dysfunction, including weakness of scapulothoracic muscles, 9 has been implicated in disorders such as shoulder (subacromial) impingement and rotator cuff strain. Shoulder pain due to these disorders has been associated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 33 publications
4
42
0
7
Order By: Relevance
“…Again, this suggests a sensory or proprioceptive influence over muscle activation simply because of the compression of the brace on the shoulder girdle, in addition to any small changes due to altered scapulothoracic position. These results are in agreement with those of Selkowitz et al, 25 who reported that scapular taping in patients with suspected impingement resulted in decreased UT amplitude and increased LT amplitude during reaching tasks. In their Kinesio Taping study, Hsu et al 23 also found EMG amplitude changes with the application of tape regardless of tension, but the direction of change was different for some of the EMG variables tested.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Again, this suggests a sensory or proprioceptive influence over muscle activation simply because of the compression of the brace on the shoulder girdle, in addition to any small changes due to altered scapulothoracic position. These results are in agreement with those of Selkowitz et al, 25 who reported that scapular taping in patients with suspected impingement resulted in decreased UT amplitude and increased LT amplitude during reaching tasks. In their Kinesio Taping study, Hsu et al 23 also found EMG amplitude changes with the application of tape regardless of tension, but the direction of change was different for some of the EMG variables tested.…”
Section: Discussionsupporting
confidence: 93%
“…Although we make no definitive recommendations based on this single study, the accumulating body of literature does suggest some benefit when using bracing or taping to alter scapular motion, muscle activation, and posture in both symptomatic and at-risk patient populations (eg, overhead athletes, patients with poor posture). 11,22,23,[25][26][27]41 Given the publication of randomized clinical trials 24,28 in which the authors found that scapular taping and bracing does assist in recovery after impingement syndromes, bracing might be a useful method for improving patient outcomes during rehabilitation. In the future, researchers should continue to examine the differential improvement due to mechanical braces (tensioned straps) versus tactile feedback braces (compression sleeves or garments, padding) and the potential differences in strap placement and application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This poor understanding contributes to the variations in the taping techniques used by different clinicians. For example many application techniques have been presented in the literature for the management of SIS alone [Host, 1995, Hsu et al, 2009, Kalter et al, Kaya et al, 2011, Lewis et al, 2005b, Selkowitz et al, 2007, Smith et al, 2009, Thelen et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The placement of the electrodes on the upper trapezius and medial deltoid muscles followed the SENIAM positioning recommendations (20) . Since the placement of the electrodes to the serratus anterior followed the recommendations of Selkowitz et al (21) . The reference electrode was positioned in the right clavicle.…”
Section: Methodsmentioning
confidence: 99%